How the Teacher’s Efforts to Instilling Responsibility Character in Learning from Home Era? - Alifiyarti, Tissa; Wuryandani, Wuri; Retnawati, Heri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The Covid-19 pandemic has caused the student learning process to be carried out from home. In the implementation of Learning from Home, the teacher's direct control over the student's learning process is reduced. These are challenges for teachers to try instill character, especially responsibility. The character of responsibility is reflected in the behavior of students who have self-awareness in seriously carrying out their duties and obligations. This study aims to describe the teacher’s efforts made in instilling the character of responsibility. The type of research is qualitative research with approach of phenomenology. The data were collected by giving open questionnaires. The subject research were 10 elementary school teachers in the District of Wates. Data analysis was performed using stages, namely data reduction, the relationship between themes, and verification. The results showed that the teacher's efforts to instill a character of responsibility were started from the planning, implementation, and assessment stages, which were integrated into the learning process. So that, those three stages show the various efforts made by teachers in instilling the character of responsibility. All the efforts that have been made by the teacher are very important to know as material for reflection or improvement so that the quality of learning in transferring the value of life is well-maintained even though the learning is conducted from home.